Pengaruh Biaya Corporate Social Responsibility Dan Struktur Modal Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Moderasi - Pradnyani, I Gusti Agung Arista; Rahayu, Nila; Anwar, Adrianda; Muhtarom, Zamroni Alpian; Febriyanti, Kadek Ayu; Fhiratullah, Aditya (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2025)
Purpose – This study aims to analyze the effects of Corporate Social Responsibility (CSR) costs and capital structure on firm value. In addition, it examines the role of financial performance, proxied by Return on Equity (ROE), as a moderating variable in these relationships, focusing on the mining sector in Indonesia. Novelty – The novelty of this research lies in employing profitability (ROE) as a moderating variable to simultaneously test the effects of CSR costs and capital structure on firm value. The emphasis on CSR costs (rather than disclosure) and the specific context of the mining sector subject to strict environmental regulations provide a more relevant and focused analytical dimension. Method – This research adopts a quantitative approach with an associative and causal design. Secondary data were obtained from annual and sustainability reports of mining companies listed on the Indonesia Stock Exchange for the 2020–2023 period, analyzed using moderated regression analysis (MRA) with t-tests, F-tests, and adjusted R². Findings – The results show that CSR costs have a positive and significant effect on firm value, while capital structure (DER) has a negative and significant effect. Furthermore, ROE moderates the effects of CSR costs and DER on firm value, where higher profitability strengthens the positive impact of CSR and mitigates the negative perception of leverage among investors. Limitations and Implications – This study is limited to the mining sector and a short observation period, which restricts the generalizability of its findings. Nevertheless, the results offer insights for managers to optimize CSR and capital structure, guide investors in evaluating long-term prospects, and support regulators in formulating transparency and sustainability policies.